The problem of the local in philosophical tradition and in modern philosophy of culture - Borodenko, O. V.; Бороденко, Олег Віталійович; Borodenko, Oleh; Borodenko, Oleh V.; Бороденко, О. В. (Одеса, 2020)
The present article is concerned with the problem of the local in the history of philosophy and in contemporary philosophy of culture. It emphasizes the relevance and interdisciplinary essence of this problem. The evolution of the concepts “local” and “locality” in classical and contemporary philosophy (by the example of the concepts of individual thinkers) is traced, and the meaning of these concepts for understanding the contemporary cultural context is determined. So, in particular, the development of ideas about the localization of an object in space in ancient philosophy (in Plato) is traced. The problem of the local in non-classical and post-non-classical philosophy is considered in connection with the problem of the crisis of cultural values. An attempt is made to define the concept of “locality” as a cultural phenomenon based on the analysis of the works of P. Sloterdijk, I. Hassan, J. Baudrillard and others, as well as the latest scientific publications. Emphasis is placed on analyzing the problem of the local as a philosophical concept, and at the same time, the phenomenon of culture, in the framework of postmodern ideas, the theory of cultural globalization, in the microspherology of P. Sloterdijk. The principle of “indetermanence” by I. Hassan, which most fully reveals the postmodern rejection of hierarchical structuring of culture and the process of transition from centering to scattering, to peripheral dislocation of cultural objects and phenomena, is considered as a kind of “methodological basis” of the analysis of locality as a cultural phenomenon. Locality is defined by the author of the article as “a certain holistic microworld (microsphere) formed by a person or a group of people as part of his (their) lifeworld and accumulating key values, ideas, symbols, etc., that are particularly significant for these people”. The main features of locality as a cultural phenomenon are considered: a) attachment to a particular place (locus); b) locality is at the same time a fragment of the world, the cosmos and a holistic microworld that lives by its own laws; c) spatiality and temporality, chronotopicity; d) dynamic and historic; e) anthropological, centered around a person or a group of people; f) symbolism.

У статті розглядається проблема локального в історії філософії і в сучасній філософії культури. Підкреслюються актуальність і міждисциплінарний характер цієї проблематики. Простежується еволюція концептів «локальне» і «локальність» у класичній і сучасній філософії (на прикладі концепцій окремих мислителів), а також ви- значається значення цих понять для осмислення сучасного культурного контексту. Так, зокрема, простежується розвиток уявлень про локалізацію об’єкта в просторі в античній філософії (у Платона). Проблема локального в некласичній і постнекласичній філософії розглядається в контексті кризи культурних цінностей. На основі аналізу робіт П. Слотердайка, І. Хассана, Ж. Бодріяра та інших, а також останніх наукових публікацій робиться спроба дати визначення поняття «локальність» як культурного феномена. Акцентується увага на аналізі проблеми локального як філософського концепту, а також як феномена культури в рамках постмодерністських концепцій, теорії культурної глобалізації, в мікросферологіі П. Слотердайка. Принцип “indetermanence” І. Хассана, який найбільш повно розкриває постмодерністську відмову від ієрархічного структурування культури і процес переходу від центрування до «розкидання», до периферійної дислокації культурних об’єктів і явищ, розглядається як так зване методологічне підґрунтя локальності як феномена культури. Локальність визначається автором статті як «певний цілісний мікросвіт (мікросфера), що утворений людиною або групою людей як частина його (їх) життєвого світу і який акумулює ключові, особливо значущі для людей цінності, ідеї, уявлення, символи тощо у певній сфері людської життєдіяльності». Розглядаються основні характеристики локальності як куль- турного явища, а саме належність до певного місця (локуса); фрагментарний характер (локальність – це фрагмент світу, космосу і цілісний мікросвіт, що живе за своїми законами); просторово-часовий характер, хронотопічність; динамічність та історичність; антропологічність, тобто центрованість навколо людини або групи людей; символічний характер.
Borodenko O. V. The problem of the local in philosophical tradition and in modern philosophy of culture / O. V. Borodenko // Актуальні проблеми філософії та соціології : Науково-практичний журнал / Голов. ред. С. Г. Секундант, відпов. ред. Д. В. Яковлев ; Міністерство освіти і науки України ; Національний університет "Одеська юридична академія". - Одеса, 2020. - Вип. 27. - С. 3-7. DOI https://doi.org/10.32837/apfs.v0i27.911
Keywords: philosophy of culture; locality; localization; the problem of the local in philosophy; microsphere; indetermanence.; філософія культури; локальність; локалізація; проблема локального у філософії; мікро-сфера; “indetermanence”; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects